2016
DOI: 10.1097/jcn.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Pilot Intervention Study for Young Adults at Risk for Cardiovascular Disease Based on Their Family History

Abstract: Background Lifestyle choices have a significant impact on cardiovascular disease (CVD) risk. Interventions to promote a heart-healthy lifestyle in young adults at long-term high-risk for CVD are needed to decease the burden of CVD. However, few interventions with this purpose have been developed. Objective Examine the effect of a pilot intervention in young adults with a family history of CVD that used three-generation pedigrees, risk factor information, and counseling on heart disease knowledge, perceived C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A survey study examined young adults (aged between 18-29) and found that compared with younger adults, older adults tended to have more positive attitudes regarding the power of FHH on personal health outcomes, and are more likely to report an interest in using FHH collection tools [45]. Furthermore, among limited FHH research focused on young adult population, the majority of their participants were female [4,7,14,15,45]. This may explain why these groups in our study might be more motivated to seek FHH education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey study examined young adults (aged between 18-29) and found that compared with younger adults, older adults tended to have more positive attitudes regarding the power of FHH on personal health outcomes, and are more likely to report an interest in using FHH collection tools [45]. Furthermore, among limited FHH research focused on young adult population, the majority of their participants were female [4,7,14,15,45]. This may explain why these groups in our study might be more motivated to seek FHH education.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies suggested that an accurate and comprehensive FHH can motivate individuals to adopt healthy behaviors, such as exercise, healthy eating, and undergoing regular medical screenings [4][5][6][7][8][9][10][11][12]. Existing FHH-based health interventions targeting the young adult population [4,7,[13][14][15] also demonstrated that FHH interventions can successfully increase participants' knowledge towards FHH, increase their understanding towards personal disease susceptibility, and motivate the adoption of healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Other study launched a holistic approached intervention to improve physical activity, environment and healthy food for three years and claimed that Body Mass Index (BMI) and fitness has considerably improved among school students [16]. Pilot study on individuals with a positive family history of CVD desired results have been depicted by improved and healthy lifestyle among respondents after delivering informative lectures [17]. A positive impact of health education intervention was achieved in a study appropriate communication methods can increase the impact of HE and prognosis of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 15 was selected for feasibility as (a) CH has an average 80 discrete admissions annually; (b) a clinical estimate based on retrospective chart review found that approximately half of admissions met this study’s criteria; (c) the hospital moved locations during our recruitment year, disrupting recruitment for approximately 1 month and (d) based on existing pilot studies, this sample size would allow the team to assess the feasibility and acceptability of intervention components across diverse experiences 34 35…”
Section: Methodsmentioning
confidence: 99%